A Meta-Analysis on the Effect and Safety of LCZ696 in the Treatment of Hypertension. (22nd March 2021) - Zheng, Li; Xia, Binbin; Zhang, Xuqian; Zhao, Yan
Abstract : Objectives . To systematically evaluate the differences in effect and safety of LCZ696 and angiotensin receptor blockers (ARBs) in the treatment of hypertension. Methods . We searched PubMed, Cochrane, Web of Science, and Ovid, collected randomized controlled trials (RCTs) about the effect and safety of LCZ696 and ARBs in hypertensive patients, extracted relevant data and evaluated the quality of the included literature according to the RCT quality evaluation standard recommended by Cochrane Reviewer's Handbook, using RevMan 5.3, and performed meta-analysis. Results . Eight RCTs studies were included, with a total of 4313 patients. Compared with ARBs, LCZ696 can better reduce systolic blood pressure (msSBP) (WMD −4.29 mmHg; 95% CI: −5.37 to −3.21; P < 0.001), diastolic blood pressure (msDBP) (WMD −1.87 mmHg; 95% CI:−2.38 to −1.36; P < 0.01), ambulatory systolic blood pressure (maSBP) (WMD −3.37 mmHg; 95% CI:−4.26 to −2.47; P < 0.01), and ambulatory diastolic blood pressure (maDBP) (WMD −1.47 mmHg; 95% CI: −1.97 to −0.97; P < 0.01). In terms of safety, LCZ696 is basically the same as ARBs, but LCZ696 is more likely to cause cough than ARBs (OR = 2.38; 95% CI: 1.27 to 4.47; P < 0.01). Conclusion . LCZ696 can significantly reduce the blood pressure level of patients with hypertension, but it is necessary to pay attention to whether the patient will experience coughing after taking the drug.